Mueller-matrix diagnostics of optical properties inherent to polycrystalline networks of human blood plasma - Ushenko, Yu.A.; Olar, O.I.; Dubolazov, A.V.; Balanetskaya, V.O.; Unguryan, V.P.; Zabolotna, N.I.; Oleinichenko, B.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
This work is aimed at studying the possibilities of Mueller-matrix diagnostics applied to optically anisotropic birefringent polycrystalline networks inherent to amino acids in human blood plasma. Determined here are interrelations between statistical moments of the first to fourth orders as well as fractal dimensionalities that characterize coordinate distributions of blood plasma Mueller-matrix elements and the physiological state of a human organism.